Distribution of mangrove health in the coastal area of Maros Regency in 2021 based on Sentinel 2 satellite imagery - Muh Faisal Mappiasse; Muliana Djafar; Reza Asra (Foresty Faculty of Hasanuddin University, 2022)
Changes in the area of mangroves in the coastal area of Maros Regency have been degraded from year to year. Various problems that often occur cause a decrease in the distribution and quality of mangrove community health. This happens because there is still pollution and external disturbances which make the quality of the mangroves decrease. Therefore, it is important to know the condition of mangrove distribution to find the latest information and baseline data for area managers. The purpose of this study was to obtain information on the extent and type of mangrove health, as well as identify the types of mangrove damage in the coastal area of Maros Regency in 2021. This research method used (1) supervised classification, to obtain mangrove distribution, (2) analysis of mangrove health using the normalized difference algorithm vegetation Index, (3) map overlay, mangrove distribution map, administrative map, and mangrove health index map, (4) validation of mangrove health data through an assessment of mangrove conditions based on the distribution of observational plots in a proportionate stratified with random sampling. Mangrove areas are found in the coastal areas of Maros Regency and are scattered in Marusu District, Maros Baru District, Lau District, Bontoa District with an area of 131.87 ha, 95.59 ha, 85.37 ha, and 60.01 ha, respectively. Mangrove health is divided into 5 categories, namely excellent, good, normal, bad, and awful with an area of 100.73 ha, 240.43 ha, 1.99 ha, 9.5 ha, and 20.2 ha, respectively. While mangrove damage based on 30 sample points, 6 types of damage were identified, namely changed leaves, damaged shoot leaves and shoots, broken/dead branches, open wounds, resinosis, and broken stems with percentages of 29.91%, 19.63%, 17.76%, 16.82%, 12.15%, and 3.74% respectively.